The prevalence of sight-threatening uveitis in Scotland. Issue 1 (17th August 2006) - Williams, G J; Brannan, S; Forrester, J V; Gavin, M P; Paterson-Brown, S P; Purdie, A T; Virdi, M; Olson, J A
Abstract : Aim: To identify and quantify the prevalence of patients with uveitis receiving systemic immunosuppression in Scotland. Methods: Anonymised data were prospectively collected on all patients with uveitis requiring systemic immunosuppression. Seven health boards participated over a 4-month period between 1 August 2005 and 30 November 2005. Results: 373 patients were identified, of whom 205 (55%) were female. The mean age was 46.4 (range 7–97 years). Using the data from the seven participating health boards, an estimated Scottish prevalence of 9 per 100 000 was calculated. Prevalence varied between 2 and 59 per 100 000. In National Health Service Grampian, all patients with uveitis, whether sight-threatening or not, are followed up at a specialist clinic. Extrapolating this figure to Scotland gives a prevalence of 25 per 100 000. Discussion: The data from National Health Service Grampian suggest that there is a significant shortfall in the number of patients identified by survey. If the "missing population" exists, then where are they? Some might be receiving appropriate treatment at non-specialist clinics, although simple under-reporting may play a part. Greater concern is for those patients receiving inappropriate treatment for their uveitis, or for those within the community who are either oblivious to or in self denial of their condition.